Critical & Creative Thinking Ability given the Inquiry Component in Elementary School Science Lessons - Sukma, Ely Sarantika; Raharjo, Tri Joko; Cahyono, Adi Nur (Thinking Skills and Creativity Journal, 2022)
The 21st-century skills are critical thinking skills and creative thinking skills. These skills are needed by someone to be successful in facing challenges, an increasingly complex and uncertain life, and to be successful in life and career in the world of work. This study aims to analyze critical and creative thinking skills in terms of the inquiry component in science learning in elementary schools. The research sample is elementary school students, with a total of 31 students. Data collection techniques used in this study were observation, tests, interviews, and documentation. The experimental research method used in this research is quasi-experimental. Quasi-experimental is used so that researchers can analyze the differences between the two treatments in the control class and the experimental class. The research design used was a non-equivalent control group design. The results of the analysis of critical and creative thinking skills for the control class inquiry model were 45.3% and 54.7%. In comparison, the experimental class obtained 65.5%, so the influence of the inquiry model on experimental class students is greater than the control class. The inquiry model has a positive effect on critical and creative thinking skills. With this research, the inquiry model can improve the critical thinking skills and creative thinking of fifth-grade elementary school students in science learning.